An Evidence‐Based Unified Definition of Lifelong and Acquired Premature Ejaculation: Report of the Second International Society for Sexual Medicine Ad Hoc Committee for the Definition of Premature Ejaculation. (1st June 2014) - Serefoglu, Ege Can; McMahon, Chris G.; Waldinger, Marcel D.; Althof, Stanley E.; Shindel, Alan; Adaikan, Ganesh; Becher, Edgardo F.; Dean, John; Giuliano, Francois; Hellstrom, Wayne J.G.; Giraldi, Annamaria; Glina, Sidney; et al.
Abstract: Introduction: The International Society for Sexual Medicine (ISSM) Ad Hoc Committee for the Definition of Premature Ejaculation developed the first evidence‐based definition for lifelong premature ejaculation (PE) in 2007 and concluded that there were insufficient published objective data at that time to develop a definition for acquired PE. Aim: The aim of this article is to review and critique the current literature and develop a contemporary, evidence‐based definition for acquired PE and/or a unified definition for both lifelong and acquired PE. Methods: In April 2013, the ISSM convened a second Ad Hoc Committee for the Definition of Premature Ejaculation in Bangalore, India. The same evidence‐based systematic approach to literature search, retrieval, and evaluation used by the original committee was adopted. Results: The committee unanimously agreed that men with lifelong and acquired PE appear to share the dimensions of short ejaculatory latency, reduced or absent perceived ejaculatory control, and the presence of negative personal consequences. Men with acquired PE are older, have higher incidences of erectile dysfunction, comorbid disease, and cardiovascular risk factors, and have a longer intravaginal ejaculation latency time (IELT) as compared with men with lifelong PE. A self‐estimated or stopwatch IELT of 3 minutes was identified as a valid IELT cut‐off for diagnosing acquired PE. On this basis, the committee agreed on a unified definition of both acquired and lifelong PE as a male sexual dysfunction characterized by (i) ejaculation that always or nearly always occurs prior to or within about 1 minute of vaginal penetration from the first sexual experience (lifelong PE) or a clinically significant and bothersome reduction in latency time, often to about 3 minutes or less (acquired PE); (ii) the inability to delay ejaculation on all or nearly all vaginal penetrations; and (iii) negative personal consequences, such as distress, bother, frustration, and/or the avoidance of sexual intimacy. Conclusion: The ISSM unified definition of lifelong and acquired PE represents the first evidence‐based definition for these conditions. This definition will enable researchers to design methodologically rigorous studies to improve our understanding of acquired PE.